2018
DOI: 10.1177/0272684x17749570
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Trends, and Consequences of Substance Use Among University Students: Implication for Intervention

Abstract: This study was conducted to examine the prevalence, trends, and consequences of substance use among university students. The prevalence of substance use, the trends of substance use, and the differences among sociodemographic variables in the experiences of substance use as well as the consequences of substance use among university students were assessed in this study. Using stratified sampling method, 1,156 students were chosen. Descriptive statistics, chi-square, one-way analysis of variance, and Pearson cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…Furthermore, our study revealed alcohol as the second most common drug used by students consistent with the result of a previous Nigerian study (10). In contrast, it ranked first in an Ethiopian study (19), and third in a Sudanese study (16). It is noteworthy that alcohol ranked second among the drugs assessed in our study despite alcohol being prohibited in the Muslim-dominated area on religious grounds.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, our study revealed alcohol as the second most common drug used by students consistent with the result of a previous Nigerian study (10). In contrast, it ranked first in an Ethiopian study (19), and third in a Sudanese study (16). It is noteworthy that alcohol ranked second among the drugs assessed in our study despite alcohol being prohibited in the Muslim-dominated area on religious grounds.…”
Section: Discussionsupporting
confidence: 90%
“…ose articles were specific to medical and health science college students. King Faisal University in Saudi Arabia reported student smoking prevalence at 28.1% [38] Other universities have targeted interventions, considering regional variations [39]. e possible justification for these variations could be due to the population's sociocultural values and norms as well as religious beliefs [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…In this age group, the daily use of marijuana was reported by 2.6 million users, while 3.4 million (10%) had alcohol use disorders [2]. In Europe an estimated 19.1 million young adults (aged [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] used substances in 2018 [4]; males used substances twice as much as females with cannabis being the most used substance [4].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many of these students joining the university experience a new freedom from parental and teacher supervision. They additionally become responsible for larger sums of money than ever before in their lives [15]. The combination of these factors increases the susceptibility of the new students to harmful peer influence which may lead to alcohol and substance use initiation.…”
Section: Introductionmentioning
confidence: 99%